The role of Traditional Chinese medicine in anti-HBV: background, progress, and challenges - Feilin Ge; Yan Yang; Zhaofang Bai; Lanlan Si; Xuemei Wang; Jia Yu; Xiaohe Xiao; Yan Liu; Zhigang Ren (BMC, 2023)
Abstract Chronic hepatitis B (CHB) remains a major world's most serious public health issues. Despite the remarkable effect of nucleos(t)ide analogues (NAs) in inhibiting hepatitis B virus (HBV) deoxyribonucleic acid (DNA) as the first-line drug, there are several limitations still, such as poor antigen inhibition, drug resistance, low-level viremia, restricting patients' functional cure. Due to the constraints of NAs, traditional medicines, such as traditional Chinese medicine (TCM), have become more prevalently used and researched in the clinical treatment of CHB as complementary alternative therapies. As a consequence, the review focuses on the background based on HBV's life cycle as well as the NAs' limitations, progress based on direct and indirect pathway of targeting HBV of TCM, and challenges of TCM. We found TCMs play an increasingly important role in anti-HBV. In a direct antiviral way, they regulate HBV infection, replication, assembly, and other aspects of the HBV life cycle. As for indirect way, TCMs can exert anti-HBV effects through targeting the host, including immune regulation, apoptosis, autophagy, oxidative stress, etc. Especially, TCMs have the advantages of strong antigenic inhibition compared to NAs. Specifically, we can combine the benefits of TCMs in strong HBV antigen inhibition with the benefits of NAs in targeted antiviral effects, in order to find a suitable combination of "TCM + NAs" to contribute to Chinese knowledge of the realisation of the "global elimination of HBV by 2030" goal of the World Health Organization.